2023
DOI: 10.1017/awf.2023.49
|View full text |Cite
|
Sign up to set email alerts
|

Validation of complementary non-invasive tools for stress assessment in spotted paca (Cuniculus paca)

Abstract: Monitoring the concentration of glucocorticoid metabolites (GCMs) in faecal samples is a non-invasive tool for physiological stress evaluation, particularly useful when studying wild species. However, both negative and positive stimuli (distress and eustress, respectively) can lead to a rise in glucocorticoids. Thus, besides validating whether GCM concentration in faeces reflects endogenous adrenal activity, we also need to identify behavioural indicators of distress to avoid misinterpretation. Therefore, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
2
0
Order By: Relevance
“…In Brazil, the spotted paca is farmed legally, mainly by small producers [27]. Although captive breeding of the species is considered relatively simple and promising for farmers, there is very little known about the welfare of this neotropical species in captivity (e.g., [28][29][30][31]). In a recent study, Lima et al [30] found that some vocalizations in adult pacas of both sexes are linked to their affective state and level of arousal.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the spotted paca is farmed legally, mainly by small producers [27]. Although captive breeding of the species is considered relatively simple and promising for farmers, there is very little known about the welfare of this neotropical species in captivity (e.g., [28][29][30][31]). In a recent study, Lima et al [30] found that some vocalizations in adult pacas of both sexes are linked to their affective state and level of arousal.…”
Section: Introductionmentioning
confidence: 99%